Integrating total quality management in religious education programs: a case study of Ramadan academy for outcome-based accreditation - Sarbini, Sarbini; Suhendi, Saca; Suhartini, Andewi; Muttaqin, Via Putrimawati; Maulana, Hamdan; Koswara, Ujang; Hambali, Wisnu; Suganda, Ayub (UIR Press, 2026)
Educational accreditation in the post-pandemic era has shifted toward Outcome-Based Accreditation, yet many Islamic institutions remain trapped in administrative formalities that fail to measure substantive character growth. While recent literature (2021-2024) emphasizes digital quality assurance, a critical research gap persists: there is a lack of empirical models showing how Total Quality Management can be synthesized with traditional pesantren-based curricula to meet the rigorous Graduate Competence Standards mandated by terbaru regulations like Permendikbudristek No. 28 of 2021. This study analyzes the